Sensitivity and specificity of indirect ELISA for the detection of antibody titers against BVDV from beef cattle raised in Pará State - Viana, Rinaldo Batista; Kzam, Aline Do Socorro Lima; Monteiro, Bruno Moura; Campello, Cláudio Cabral; De Moura Sousa, Eliomar; De Souza, Damazio Campos [UNESP]; Okuda, Liria Hiromi; Pituco, Edviges Maristela; Filho, José Dantas Ribeiro (Universidade Estadual de Londrina, 2017)
The aims of this study were to establish the prevalence of anti-bovine viral diarrhea virus (BVDV) antibodies (Ab) in beef cattle raised in Pará state, to compare the prevalence of seropositive animals to BVDV using a commercial indirect enzyme-linked immunosorbent assay kit (iELISA) and the virus neutralization (VN) test, and finally, to determine the sensitivity (Se) and specificity (Sp) of the iELISA for the detection of anti-BVDV Ab using VN as a gold standard. A total of 400 serum blood samples from Nelore cows aged at least 24 months from five farms in the Pará state from two mesoregions (Metropolitan Region of Belem and Northeast of Pará) were analyzed. All animals were vaccinated against brucellosis and foot-and-mouth disease. The examination of anti-BVDV Ab with VN was performed in the Laboratory of Bovine Viruses of the Biological Institute of Sao Paulo as described in the Manual of Diagnostic Tests and Vaccines for Terrestrial Animals. For VN, bovine kidney epithelial cells from the Madin Darby Bovine Kidney (MDBK) strain were used. The determinations of anti-BVDV Ab were performed with the iELISA test at the Laboratory of Immunology and Microbiology of the Federal Rural University of Amazonia according to the manufacturer's recommendations. The results were classified as follows: (a) correct positive diagnosis, (b) incorrect positive diagnosis, (c) correct negative diagnosis, and (d) incorrect negative diagnosis, according to the results obtained from VN. From the values obtained from VN and iELISA, Se [(a ÷ a + d) × 100], Sp [(c ÷ c + b) × 100], positive predictive value [(a ÷ a + B) × 100], and negative predictive value [(c ÷ c + d) × 100] were calculated for iELISA. The frequencies (%) of seropositive animals were determined and compared both between the different tests (iELISA and VN) and between the different farms (1, 2, 3, 4, and 5). The statistical analysis was performed with a significance level of 5%. The prevalence of seropositive animals was found to be different (P < 0.0001) using VN (39.25% [157/400]) and iELISA (54.50% [218/400]). It was observed that the Se and Sp of the iELISA assay were 98.72% and 74.07%, respectively. Of the total, 25.93% (63/243) of the samples were considered false-positive and 1.27% false-negative (2/157). It was concluded that the BVDV infection is present in beef cattle herds of the state of Para. Based on the speed of execution, ease of handling, and high Se of the iELISA, it is suggested that this assay can be used as a screening test for the detection of anti-BVDV Ab with the aim of eliminating infected animals from large herds of beef cattle.
Keywords: Beef cattle; ELISA; Sensibility; Specificity; Viral diarrhea; Virus neutralization